At the beginning... there was the desire. the constitution of the self in the "Character of rain": an interpretation from a psychoanalytic point of view - Rosa Durá Celma (Cuadernos de Investigación Filológica, 2013)
This paper proposes an interpretation of Amélie Nothomb´s novel "The Character of Rain" ("Métaphysique des tubes") from a literary perspective and adopts the theoretical model put forward in the lacanian psychoanalysis. From this point of view we discuss how this autofiction formalizes some of the steps involved in the subjective constitution paying special attention to the notion of desire, and how these are specified, formally and thematically, in the writing strategy the author adopts. We will examine also the impact which the symbolic order has on the building of the subject- and the way the novel plays with the focus point of view